Influence of non-covalent modification of multiwalled carbon nanotubes on the crystallization behaviour of binary blends of polypropylene and polyamide 6. Issue 6 (9th January 2015) - Mukhopadhyay, Nabaneeta; Panwar, Ajay S.; Kumar, Gulshan; Samajdar, I.; Bhattacharyya, Arup R.
Abstract : 'Agglomerated' and 'individualized' MWNTs providing varying extent of hetero-nucleation to the polymer chains. Abstract : Blends of polypropylene (PP) and polyamide 6 (PA6) with multiwalled carbon nanotubes (MWNTs) were prepared using different processing strategies in a twin-screw micro-compounder. The effect of MWNTs on the crystallization behaviour of the PP phase and the PA6 phase of the blend has been investigated through non-isothermal crystallization studies by differential scanning calorimetric analysis. Furthermore, the effect of the addition of the compatibilizer (PP- g -MA) and the modification of MWNTs (m-MWNTs) with a non-covalent organic modifier (Li-salt of 6 amino hexanoic acid, Li–AHA) has also been studied in context to the crystallization behaviour of the PP and PA6 phase in the blend. The crystallization studies have indicated a significant increase in bulk crystallization temperature of the PP phase in the blend in the presence of MWNTs. Moreover, the formation of 'trans-lamellar crystalline' structure consisting of PA6 'trans-crystalline lamellae' on MWNTs surface was facilitated in the case of blends prepared via 'protocol 2' as compared to the corresponding blends prepared via 'protocol 1'. Wide angle X-ray diffraction analysis has showed the existence of a β-polymorph of the PP phase due to incorporation of the PA6 phase in the blend. Addition of MWNTs in the blends has facilitated further β-crystalline structure formation of the PP phase. In the presence of m-MWNTs, a higher β-fraction was observed in the PP phase as compared to the blend with pristine MWNTs. Addition of PP- g -MA has suppressed the β-phase formation in the PP phase in the blend. X-ray bulk texture analysis revealed that incorporation of PA6 as well as pristine/modified MWNTs has influenced the extent of orientation of the PP chains towards specific crystalline planes in various blend compositions of PP and PA6.